2019
DOI: 10.3390/molecules24193544
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Based Hybrid Admixtures and their Role in Cement Composite Fabrication

Abstract: In this study, a technology for obtaining functional inorganic-organic hybrid materials was designed using waste polymers of natural origin, i.e., kraft lignin and magnesium lignosulfonate, and alumina as an inorganic component. Al2O3-lignin and Al2O3-lignosulfonate systems were prepared by a mechanical method using a mortar grinder and a planetary ball mill, which made it possible to obtain products of adequate homogeneity in an efficient manner. This was confirmed by the use of Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 39 publications
6
11
0
2
Order By: Relevance
“…The structure of lignin is very complex, and the degradation products depend strongly on the type of biopolymer, the bonds linking the monomers, and the moisture content. These data correlate well with those reported in previous studies [ 51 , 52 ].…”
Section: Resultssupporting
confidence: 93%
“…The structure of lignin is very complex, and the degradation products depend strongly on the type of biopolymer, the bonds linking the monomers, and the moisture content. These data correlate well with those reported in previous studies [ 51 , 52 ].…”
Section: Resultssupporting
confidence: 93%
“…With the increase in the amount of lignin in the composite, the value of compressive strength decreased, which is probably related to a greater aeration of the cement paste. Similar relationships have been reported by other researchers for lignosulfonates, hence the maximum amount of admixtures in cement composites is usually up to 0.5 wt.% in relation to cement [2, 43,44]. As the bio-admixture in the system was replaced with silica, an increase in compressive strength was observed for both 0.5 and 1 wt.% samples.…”
Section: Compressive Strength Properties With the Silica Lignin And supporting
confidence: 86%
“…The authors of publications [40][41][42][43] also observed an increase in the plasticity of mixtures with the addition of lignin or its derivatives. Kalliola et al [40] reported a beneficial effect of the admixture of oxidized lignin on the flow rate for pastes, mortars and concretes.…”
Section: Slump Test Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Agriculture and forestry waste is primarily burnt on field in order to reduce the cost of disposal. When converted into biochar, this waste can be used as a partial substitute to cement, resulting in a significant reduction in greenhouse gas emissions and improving the mechanical properties of concrete [4,5].…”
Section: Introductionmentioning
confidence: 99%